2011
DOI: 10.1142/s0218202511005362
|View full text |Cite
|
Sign up to set email alerts
|

Justification of Point Electrode Models in Electrical Impedance Tomography

Abstract: The most accurate model for real-life electrical impedance tomography is the complete electrode model, which takes into account electrode shapes and (usually unknown) contact impedances at electrode-object interfaces. When the electrodes are small, however, it is tempting to formally replace them by point sources. This simplifies the model considerably and completely eliminates the effect of contact impedance. In this work we rigorously justify such a point electrode model for the important case of having dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 20 publications
1
101
0
Order By: Relevance
“…The trace on the boundary cannot be evaluated at a point, so point measurements of voltage are undefined. However it can be shown that if the conductivity is changed only in the compliment of a neighborhood of @ the resulting voltage difference at the boundary can be evaluated at points [52].…”
Section: Measurements With Electrodesmentioning
confidence: 99%
“…The trace on the boundary cannot be evaluated at a point, so point measurements of voltage are undefined. However it can be shown that if the conductivity is changed only in the compliment of a neighborhood of @ the resulting voltage difference at the boundary can be evaluated at points [52].…”
Section: Measurements With Electrodesmentioning
confidence: 99%
“…In practice, the voltage data measured on each current-carrying electrode are excluded to avoid the contact impedance problem. Moreover, the use of difference data in the methods proposed here averts the influences of contact impedance as well as singularities caused by point electrodes [6].…”
Section: Electrode Configurationmentioning
confidence: 99%
“…[14]): Constant flux of current is maintained between two electrodes at fixed locations y + and y − . Meanwhile, the third electrode, which is moved along ∂D and not used for current injection, measures the boundary potential.…”
Section: That (53) Has a Unique Solution Inmentioning
confidence: 99%